2
$\begingroup$

I am brand new to ODE's, and have been having difficulties with this practice problem. Find a 1-parameter solution to the homogenous ODE:$$2xy \, dx+(x^2+y^2) \, dy = 0$$assuming the coefficient of $dy \ne 0$ The textbook would like me to use the subsitution $x = yu$ and $dx=y \, du + u \, dy,\ y \ne 0$ Rewriting the equation with the subsititution: $$2uy^2(y \, du + u \, dy)+(x^2+y^2) \, dy = 0$$ divide by $y^2$ $$2u(y \, du + u \, dy) + (u^2+1 ) \, dy=0$$ but after further simplification I end up getting ${dy \over y}$ which would mean I would get a logarithm after integrating, and the answer is given as $$3x^2y+y^3 = c$$ Could I get some help/hints as to how this answer was obtained?

$\endgroup$
2
$\begingroup$

The variables $y$ and $u$ can be separated from each other: $$ 2u(y \, du + u \, dy) + (u^2+1 ) \, dy=0 $$ $$ 2u\left( du + u \, \frac{dy} y \right) + (u^2+1 ) \, \frac{dy} y = 0 $$ $$ 2u\left( \frac{du} u + \frac{dy} y \right) + \left( u + \frac 1 u \right) \, \frac{dy} y = 0 $$ $$ 2 \left( \frac{du} u + \frac{dy} y \right) + \left( 1 + \frac 1 {u^2} \right) \, \frac{dy} y = 0 $$ $$ 2 \frac{du} u + 2 \frac{dy} y + \left( 1 + \frac 1 {u^2} \right) \, \frac{dy} y = 0 $$ $$ 2 \frac{du} u + \left( 3 + \frac 1 {u^2} \right) \, \frac{dy} y = 0 $$ $$ \left( 3 + \frac 1 {u^2} \right) \, \frac{dy} y = -2 \frac{du} u $$ $$ \frac{dy} y = \frac{-2 \, du/u}{3 + \frac 1 {u^2}} $$ $$ \frac{dy} y = \frac{-2 u\, du}{3u^2 + 1} $$ $$ \log|y| = - \frac 1 3 \log|3u^2 + 1| + \text{constant} $$ $$ y = (3u^2+1)^{-1/3}\cdot\text{constant} $$ $$ y^3 = \frac{\text{constant}}{3u^2+1} $$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Thank you for taking the time to write a complete and explicit answer! $\endgroup$ – mysatellite Jul 29 '15 at 0:46
2
$\begingroup$

$$2xy\mathrm dx+(x^2+y^2)\mathrm dy = 0$$

$$2xy \mathrm dx=-(x^2+y^2)\mathrm dy$$

$$\frac{dx}{dy}=-\frac{(x^2+y^2)}{2xy}$$

Now put, $x=yu \Rightarrow \mathrm dx=u\mathrm dy+y\mathrm du$, i.e. $\frac {dx}{dy}=u+y\frac{du}{dy}$

Using these substitution and after simplification a you will get that

$$\frac{2u}{3u^2+1} \mathrm du=-\frac{1}{y}\mathrm dy$$

On integration you will get that,

$$\frac{1}{3}\ln(u^2+\frac{1}{3})+\ln y=\ln c$$

$$\ln {(u^2+\frac{1}{3})y^3=\ln c^3}$$

$$(u^2+\frac{1}{3})y^3=C$$ Now replace back $u=x/y$, you will get your answer.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Yes, you get $dy/y+ 2u/(3u^2+ 1)du= 0$.

The integral of $dy/y$ is $ln(|y|)$ and the integral of $2u/(3u^2+ 1)du$, using the substitution $v= 3u^2+ 1$ so that $dv= 6udu$ or $2udu= dv/3$, is the integral of $1/v dv/3$ which is $$(1/3)ln(|v|)= (1/3)ln(3u^2+ 1)= (1/3)ln(3x^2/y^2+ 1)$$

So integrating $dy/y+ 2u/(3u^2+ 1)= 0$ becomes $$ln(|y|)+ (1/3)ln(3x^2/y^2+ 1)= C$$ or, equivalently, $-3ln(|y|)= ln(3x^2/y^2+ 1)+ C$.

Now, taking the exponential of both sides $y^{-3}= C(3x^2/y+ 1)$.

Finally, multiply on both sides by $y^3$ to get $1= C(3x^2y+ y^3)$ which is the same as $1/C= C'= 3x^2y+ y^3$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.